2017
DOI: 10.1111/eip.12426
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinicians’ awareness of psychiatric comorbidities among first–episode schizophrenia

Abstract: Background To explore the prevalence and clinicians’ awareness of psychiatric comorbidities, and to identify factors associated with current psychiatric comorbidities in first–episode schizophrenia (FES) patients. Method In this cross–sectional study, 128 patients with FES, who were in symptomatic remission, were consecutively recruited from a local early intervention clinic. All patients were interviewed using the Chinese bilingual version of the Structured Clinical Interview for Diagnostic and Statistical Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…A recent systematic review obtained pooled median point and 12month prevalence values for psychotic disorders of 3.89 and 4.03 per 1000, respectively, with a median lifetime prevalence of 7.49 per 1000 (Moreno-Küstner, Martín, & Pastor, 2018). Furthermore, psychotic disorders are frequently associated with other psychopathological conditions, both during the first episode and throughout the course of the disorder (Buckley, Miller, Lehrer, & Castle, 2009;Hoertel et al, 2019;Singh, Beniwal, Bhatia, & Deshpande, 2019;Siu, Chong, & Lo, 2018;Tsai & Rosenheck, 2013). About 40% of patients with a first psychotic episode (FPE) have a current psychic comorbidity recorded in their medical history (Siu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review obtained pooled median point and 12month prevalence values for psychotic disorders of 3.89 and 4.03 per 1000, respectively, with a median lifetime prevalence of 7.49 per 1000 (Moreno-Küstner, Martín, & Pastor, 2018). Furthermore, psychotic disorders are frequently associated with other psychopathological conditions, both during the first episode and throughout the course of the disorder (Buckley, Miller, Lehrer, & Castle, 2009;Hoertel et al, 2019;Singh, Beniwal, Bhatia, & Deshpande, 2019;Siu, Chong, & Lo, 2018;Tsai & Rosenheck, 2013). About 40% of patients with a first psychotic episode (FPE) have a current psychic comorbidity recorded in their medical history (Siu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, psychotic disorders are frequently associated with other psychopathological conditions, both during the first episode and throughout the course of the disorder (Buckley, Miller, Lehrer, & Castle, 2009;Hoertel et al, 2019;Singh, Beniwal, Bhatia, & Deshpande, 2019;Siu, Chong, & Lo, 2018;Tsai & Rosenheck, 2013). About 40% of patients with a first psychotic episode (FPE) have a current psychic comorbidity recorded in their medical history (Siu et al, 2018). Numerous studies have shown that, with respect to the general population, adults diagnosed with schizophrenia are more likely to suffer anxiety, depression, obsessive symptoms and substance use disorders (Buckley et al, 2009;Hoertel et al, 2019;Singh et al, 2019;Tsai & Rosenheck, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of such transdiagnostic overlap has also been reported in brain structural 5,6 and genetic [7][8][9] studies. Specifically, SZ diagnosis is frequently concurrent with substance use, such as smoking and drinking 10,11 , showing a prevalence of 50%, for example. Neuroimaging findings comparing substance use disorders and SZ show that they both involve reward network dysfunction related with impulsive control 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies used samples of patients with borderline personality disorder (McGirr et al., 2007; Tadic et al., 2009). One study each represented a sample of individuals diagnosed with the following disorders: OCD (Menzies et al., 2017), post‐traumatic stress disorder (PTSD; Gekker et al., 2018), binge eating disorder (Grilo et al., 2009), depression (Zimmerman et al., 2002), bipolar disorder (McElroy et al., 2001), schizophrenia (Siu et al., 2018), functional movement disorder (Epstein et al., 2016), ADHD (Edvinsson et al., 2013) and nicotine dependence (Piper et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…For all included studies, the mean values and standard deviations for current and lifetime disorders were extracted, in addition to the number of participants. Of the 27 studies included in the meta‐analysis, the authors of 11 studies were contacted in order to obtain data that had not been reported (Arnberg et al., 2013; Brown et al., 2001; Chong et al., 2012; Grilo et al., 2009; Ormel et al., 2015; Piper et al., 2010; Shaffer et al., 2007; Siu et al., 2018; Subramaniam et al., 2019; Tabet et al., 2016; Thoma et al., 2021). The statistical analyses were conducted using Comprehensive Meta‐Analysis (CMA) Version 3.…”
Section: Methodsmentioning
confidence: 99%